C2-insertion into a fullerene orifice. Issue 12 (23rd January 2023) - Hashikawa, Yoshifumi; Murata, Yasujiro
Abstract : The C2-insertion into a fullerene orifice enables an expansion of the inner space while the C2 unit originated from N -phenylmaleimide is merged with the fullerene skeleton possessing an orifice enlarged from an octagon to a decagon. Abstract : The embedment of a C n -unit into a carbon network constituting fullerene(s) potentially enables a cage-expansion. Herein, we report a C2-insertion into a fullerene orifice in which the mechanism was examined computationally. The C2-embedded open-[60]fullerene possesses an orifice enlarged from an octagon to a decagon, while the inner space was notably expanded as confirmed by the dynamic motion of the incarcerated H2 O molecule.